2013
DOI: 10.1063/1.4824445
|View full text |Cite
|
Sign up to set email alerts
|

Atomic layer deposition of ZrO2 as gate dielectrics for AlGaN/GaN metal-insulator-semiconductor high electron mobility transistors on silicon

Abstract: Atomic layer deposition of ZrO2 as gate dielectrics for AlGaN/GaN metal-insulator-semiconductor high electron mobility transistors on silicon. Applied physics letters, 103(14), 142109-.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
29
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(29 citation statements)
references
References 13 publications
0
29
0
Order By: Relevance
“…This effect is also described as dynamic behavior degradation, gate lag, drain lag, etc., which is caused by the charge trapping effect on the AlGaN surface especially in the access region between gate and drain [4-6]. In order to solve these two issues, the deposition of oxide-based dielectric such as SiO 2 [7], Al 2 O 3 [8], LaLuO 3 [9], and SrO 2 [10,11] and dielectric stack such as SiN/Al 2 O 3 [12] as gate dielectric layer and passivation layer in the access region simultaneously is widely adopted. But it has been revealed that the introduction of oxide-based dielectric is likely to form Ga-O bond which is thought as one of interface sources leading to current collapse [13].…”
Section: Introductionmentioning
confidence: 99%
“…This effect is also described as dynamic behavior degradation, gate lag, drain lag, etc., which is caused by the charge trapping effect on the AlGaN surface especially in the access region between gate and drain [4-6]. In order to solve these two issues, the deposition of oxide-based dielectric such as SiO 2 [7], Al 2 O 3 [8], LaLuO 3 [9], and SrO 2 [10,11] and dielectric stack such as SiN/Al 2 O 3 [12] as gate dielectric layer and passivation layer in the access region simultaneously is widely adopted. But it has been revealed that the introduction of oxide-based dielectric is likely to form Ga-O bond which is thought as one of interface sources leading to current collapse [13].…”
Section: Introductionmentioning
confidence: 99%
“…The amorphous state of ZrO 2 ( a ‐ZrO 2 ) has various important technological applications as well . The theoretical investigations based on first‐principles molecular dynamics (MD) simulations have revealed that it has a local structure analogous to that of the baddeleyite phase.…”
Section: Introductionmentioning
confidence: 99%
“…The amorphous state of ZrO 2 (a-ZrO 2 ) has various important technological applications as well. 5,[28][29][30] The theoretical investigations based on first-principles molecular dynamics (MD) simulations [31][32][33][34] have revealed that it has a local structure analogous to that of the baddeleyite phase. The crystallization behavior of a-ZrO 2 at high temperatures has been also experimentally explored.…”
Section: Introductionmentioning
confidence: 99%
“…Excellent electrical characteristics of GaN-based MISHEMTs utilizing ZrO 2 as gate dielectrics are reported recently. [9][10][11][12][13][14] In addition, from device fabrication point of view, post-deposition annealing (PDA) could serve as an effective way to improve the interfacial properties between high-k dielectric layer and GaN-based substrates. However, even though AlGaN has been extensively utilized in GaN HEMTs, few studies have been carried out on the interfacial structure and chemical bonding states at the interface between ZrO 2 and AlGaN subjected to post-deposition annealing.…”
mentioning
confidence: 99%